Simulation results of liquid slosh in a partially filled cylindrical tank - Hussain Shah, Qasim; Abid, Hasan M.; Rosli, Adib (IIUM Press, 2011)
A 3D model of liquid slosh inside a partially filled tank is done by using Smoothed Particle Hydrodynamics (SPH) method of LS-DYNA software package. The validation of the simulation model was performed against the experimental results for various filled of water volume in tank. Majority of the previous slosh analyses have thus been made in the scope of laminar flows. The results of the strain are discussed in the following sections of liquid fill levels of 50 % and 70%. Moreover the discussion will focus also on the liquid slosh behaviors of the simulation model of SPH which represents the water inside the cylindrical tank, and the figure shows the liquid slosh at different time histories of 0, 10, 20, 30, 40, 50,60,70 ms.